The crystal structure of catena-poly[bis(1-ethylimidazole-k1 N)-(μ 2-benzene-1-carboxyl-3,5-dicarboxylato-κ 2 O, O′)zinc(II)], C19H20N4O6Zn - Guo Ya-Fei; Chen Bao-Kuan (Zeitschrift für Kristallographie - New Crystal Structures)
C19H20N4O6Zn, monoclinic, P21/n (no. 14), a = 11.7411(7) Å, b = 13.7831(9) Å, c = 13.5425(10) Å, β = 97.564(2)∘ $97.564{(2)}^{° }$ , V = 2172.5(3) Å3, Z = 4, R gt(F) = 0.0645, wR ref(F 2) = 0.1643, T = 298 K.